Epidermal inclusion cyst of breast diagnosed on fine needle aspiration cytology: a retrospective study - Singh, Gajender; Brar, Komal; Ralli, Megha; Kalra, Rajnish; Chhabra, Sonia; Kataria, Sant Prakash; Kalyan, Sonu (International Journal of Research in Medical Sciences, 2017)
Background: Epidermal inclusion cyst (EIC) is a rare benign condition of breast. Patient presents with palpable breast lump and needs to be differentiated from other breast lesions. This study included cases of epidermal inclusion cyst of breast (EICB) diagnosed on fine needle aspiration cytology (FNAC) and their correlation with histopathological findings. Methods: Study was conducted in a retrospective manner over a period of 2 years. 8 Patients who presented with breast lump and were cytologically diagnosed as EIC were included in the study. Cytological features were suggestive of EIC or infective EICB. Histopathological confirmation was done. Female: Male ratio in the study was 7:1 with an age range of 35 to 54 years. Radiological investigations favoured benign lesions in 5 cases and tubercular collection in one case. Results: FNAC was performed and May-Grunwald-Giemsa stained smears showed numerous anucleate squames and mature squamous epithelial cells in a clean or inflammatory background. Diagnosis of EICB or infective EICB was made on cytology. Diagnosis was confirmed histologically in 6 cases. Conclusions: Asymptomatic lesions do not require biopsy and treatment. Follow-up is sufficient if typical clinical and radiological findings are there. But in symptomatic cases, excision should be done followed by histopathological confirmation to rule out malignant lesion. Diagnosis should be made on FNA whenever associated with characteristic pultaceous aspirate and cytological findings.